(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the evolution and current state of Uzbek contemporary music, highlighting its stylistic diversity, cultural foundations, technological influences, and socio-artistic transformations. It analyzes the interaction between traditional musical heritage and modern genres, the development of new compositional practices, the impact of digital media, and the growing role of independent artists in shaping the national soundscape. The study demonstrates how contemporary Uzbek music reflects global trends while preserving regional identity, and discusses the challenges and opportunities affecting its future development.